OPSOCLONUS-MYOCLONUS-ATAXIA SYNDROME (OMAS) DUE TO ORGANOPHOSPHATE TOXICITY: CASE REPORT OF A RARE ASSOCIATION - Dur-e-Sabeh; Butt, Nauman Ismat; Ghoauri, Muhammad Sohail Ajmal; Ali, Asfand Yar; Qaisar, Fahad; Javed, Muhammad Umair (Journal of Ayub Medical College Abbottabad, 2025)
Opsoclonus-Myoclonus-Ataxia Syndrome (OMAS) is a rare neurological disorder characterized by severe ataxia, multifocal muscle jerky movements and rapid eye oscillatory movements rarely seen as a consequence of organophosphate exposure. A 19-year-old gentleman presented with 2-day history of sudden onset uncontrollable jerky movements of all four limbs, dizziness and vertigo, difficulties in sitting and walking characterized by side-way swaying and increased tendency to fall. There was history of palpitations, vomiting, diarrhea, increased urination, lacrimation and salivation. Four days prior to presentation, there was accidental exposure to chlorpyrifos. On examination, pooling of tears, dribbling of saliva, hypertension, tachycardia, miosis, opsoclonus, myoclonus and ataxia were noted. He was admitted and started on intravenous atropine. MRI scan was done which demonstrated normal cerebellum. He was diagnosed with OMAS caused by Organophosphate Toxicity. By the time of discharge, he was clinically stable and asymptomatic.